A new approach of microalgal biomass pretreatment using deep eutectic solvents for enhanced lipid recovery for biodiesel production. (October 2016) - Lu, Weidong; Alam, Md. Asraful; Pan, Ying; Wu, Jingcheng; Wang, Zhongming; Yuan, Zhenhong
Highlights: A new approach of microalgae biomass pretreatment has been proposed. Lipid recovery enhanced significantly after aDES pretreatment. Lipids from aDESs pretreated biomass are suitable for biodiesel production. Abstract: The biomass of Chlorella sp. was pretreated with three different aqueous deep eutectic solvents (aDESs), i.e. aqueous choline chloride-oxalic acid (aCh-O), aqueous choline chloride-ethylene glycol (aCh-EG) and aqueous urea-acetamide (aU-A). The effect of aDESs pretreatment of microalgae biomass was evaluated in terms of lipid recovery rate, total carbohydrate content, fatty acid composition, and thermal chemical behavior of biomass. Results indicated that, lipid recovery rate was increased from 52.03% of untreated biomass to 80.90%, 66.92%, and 75.26% of the biomass treated by aCh-O, aCh-EG and aU-A, respectively. However, there were no major changes observed in fatty acid profiles of both untreated and treated biomass, specifically palmitic acid, palmitoleic acid and stearic acid under various pretreatments. Furthermore, characterizations of untreated and treated biomass were carried out using Fourier transform infrared (FTIR), thermogravimetry analysis (TGA) and scanning electron microscope (SEM) to understand the enhanced lipids recovery.